2016
DOI: 10.1002/mrm.26478
|View full text |Cite
|
Sign up to set email alerts
|

Renal MR angiography and perfusion in the pig using hyperpolarized water

Abstract: DNP AbstractPurpose: To study hyperpolarized water as an angiography and perfusion tracer in a large animal model. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The model-free deconvolution has previously been applied in hyperpolarized experiments, yielding accurate 13 C-MTT maps with a minor deviation originating from the relaxation decay of the tracer 29 . These results are further supported by the recent hyperpolarized water perfusion in the porcine kidney 42 , demonstrating that the accurate use of formalism can determine the perfusion of the kidney.…”
Section: Discussionsupporting
confidence: 60%
“…The model-free deconvolution has previously been applied in hyperpolarized experiments, yielding accurate 13 C-MTT maps with a minor deviation originating from the relaxation decay of the tracer 29 . These results are further supported by the recent hyperpolarized water perfusion in the porcine kidney 42 , demonstrating that the accurate use of formalism can determine the perfusion of the kidney.…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies have also reported the utilization of HP urea and HP water to image renal perfusion . For example, in a rat model of IRI, Nielsen et al showed a significant reduction in the HP 13 C, 15 N–urea distribution in the injured kidney, which could be a result of a combination of reduced blood flow and altered urea transport.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a rat model of IRI, Nielsen et al showed a significant reduction in the HP 13 C, 15 N–urea distribution in the injured kidney, which could be a result of a combination of reduced blood flow and altered urea transport. Ardenkjaer‐Larsen and co‐workers demonstrated in swine that renal cortical perfusion can be measured using high‐contrast dynamic HP water imaging. Future studies combining multiple HP probes to simultaneously assess perfusion and metabolism are warranted to further interrogate the multiple molecular events that occur during progressive kidney injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was similar to a previously reported . In short, the pig was anesthetized with an initial dose of intravenous (IV) propofol 12 mg, intubated, and mechanically ventilated using a 60% O 2 ‐air mix using a commercially available Avance respirator system with a built‐in CO 2 and O 2 gas monitoring unit (GE Healthcare, Brøndby, Denmark).…”
Section: Methodsmentioning
confidence: 99%